2021
DOI: 10.1186/s12889-020-10127-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring wealth-related inequalities in maternal and child health coverage in Latin America and the Caribbean

Abstract: Background Maternal and child health have shown important advances in the world in recent years. However, national averages indicators hide large inequalities in access and quality of care in population subgroups. We explore wealth-related inequalities affecting health coverage and interventions in reproductive, maternal, newborn, and child health in Latin America and the Caribbean. Methods We analyzed representative national surveys from 15 countr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…The burdens of neonatal disorders were not balanced in five SDI subareas, which might be due to unequal access to health protection and medical resources ( 21 ). The greatest decline in ASDR and ASR-DALYs was noticed in the high-middle-SDI regions, which was inseparable from reasonable input in the enhancement of the medicare health systems, continued medical investment, and comprehensive neonatal care ( 2 ). By comparison, the ASDR and ASR-DALYs showed the smallest decrease in low-SDI regions at the same research time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The burdens of neonatal disorders were not balanced in five SDI subareas, which might be due to unequal access to health protection and medical resources ( 21 ). The greatest decline in ASDR and ASR-DALYs was noticed in the high-middle-SDI regions, which was inseparable from reasonable input in the enhancement of the medicare health systems, continued medical investment, and comprehensive neonatal care ( 2 ). By comparison, the ASDR and ASR-DALYs showed the smallest decrease in low-SDI regions at the same research time.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the study on the burden of neonatal disorders is mostly focused on a single health problem or independent risk factors. Although past research has reported the global incidence and death rates of neonatal disorders ( 2 ), the continuous changes and disability-adjusted life years (DALYs) of neonatal disorders need to be clarified. Their geographical distribution and long-term tendencies have not been explained, and the association between socioeconomic status and human development index in the regional and national contexts also needs to be further clarified.…”
Section: Introductionmentioning
confidence: 99%
“…El MINSA, siguiendo las indicaciones de la Organización Mundial de la Salud, asume un mínimo de seis controles prenatales ( 11 , 24 ). Empero, con niveles de cobertura de atención de calidad que dejan aún brechas, la disminución de la desigualdad en el número de controles resultará insuficiente para alcanzar las metas de salud esperadas ( 13 , 15 ). Para los años analizados, se constató un paulatino cierre de las brechas entre las mujeres peruanas de las zonas rurales y urbanas en la cantidad y calidad de controles.…”
Section: Discussionunclassified
“…26 Ensuring that all children have access to vaccines is a challenge, which involves identifying and dealing with vaccination gaps in terms of accessibility and individual determinants, especially during health crises. 38 , 39 Additional efforts are needed to ensure continuity of infant vaccination services and to ensure that unvaccinated infants are brought up to date as soon as possible. Future research should include an analysis of infant vaccination coverage with data from demographic surveys at the level of the different subgroups of the population, evaluating inequalities according to the sex of the child, place of residence, level of education of the mother and socioeconomic level of the household, among others.…”
Section: Discussionmentioning
confidence: 99%